(untitled) (Research, Society and Development, 2025)
This study aimed to evaluate the association between body dissatisfaction and body mass index (BMI) in elementary school students. The sample consisted of 38 schoolchildren, with a mean age of 8.44 years (±1.10), of which 57.9% were male and 42.1% were female. Body dissatisfaction was assessed using the Software for Body Perception Assessment (S.A.P.E.C.O), and nutritional status was determined by BMI. The results revealed a high prevalence of body dissatisfaction (84.2%), with significant differences between sexes: girls showed greater dissatisfaction related to excess weight (41.2%), while boys demonstrated greater dissatisfaction with thinness (73.3%). No statistically significant association was found between BMI and body dissatisfaction (p > 0.05). It is concluded that body dissatisfaction is a prevalent phenomenon among schoolchildren, with differences associated with sex, highlighting the need for educational and psychological interventions to promote a positive self-image and prevent eating and emotional disorders.